RE-ACTUALIZATION THOUGHT KH. HASYIM ASY'ARI ABOUT NATIONAL UNITY AND ITS URGENCY IN FACING THE COVID-19 PANDEMIC (Jurnal Sosial Humaniora dan Pendidikan, 2022)
All religions teach their adherents to do good and create unity with solid brotherly ties in the life of the nation and state. In writing this article, several problem formulations are the subject of discussion, including; (1) the re-actualization thoughts of KH Hasyim Asy'ari on national unity; and (2) the urgency of national unity during the Covid-19 pandemic to reflect on the history of the founding of the Indonesian nation and state, which was built on unity and integrity with a complete sense of nationalism that accommodates common interests without discrimination. Then, this article is a study of library research with a qualitative type based on complex and comprehensively identified social phenomena through a descriptive-analytic approach. Furthermore, the results of this article state that KH. Hasyim Asy'ari is a national figure whose thoughts are widely used as the basis for acting in the face of various imperialist powers with the spirit of national unity, which different groups accept. Once fueled the nature of national unity. In today's life, KH. Hasyim Asy'ari can be practised and imitated to rise together against the Covid-19 pandemic by being united through the spirit of solidarity and national brotherhood to complement each other to create a good and prosperous order during the Covid-19 pandemic.